ClickIn: a flexible protocol for quantifying mitochondrial uptake of nucleobase derivatives. Issue 2 (6th April 2017) - Hoogewijs, Kurt; James, Andrew M.; Smith, Robin A. J.; Abendroth, Frank; Gait, Michael J.; Murphy, Michael P.; Lightowlers, Robert N.
Abstract : There is an increasing interest in targeting molecules to the mitochondrial matrix. Many proteins are naturally imported through the translocase complexes found in the outer and inner mitochondrial membranes. One possible means for importing molecules is therefore to use a mitochondrial pre-protein as a vector and assess what forms of molecules can be attached to the pre-protein as cargo. A major difficulty with this approach is to ensure that any chimaeric molecule does indeed access the mitochondrial matrix and does not merely associate with the mitochondrial membranes. We have recently demonstrated that click chemistry can be used both to demonstrate convincingly mitochondrial import of a peptide–peptide nucleic acid conjugate and also to quantify the mitochondrial uptake for specific synthetic conjugates. We now report an adaptation of the synthesis to facilitate simple quantification of multiple molecules and hence to calculate the efficiency of their mitochondrial import.